Reproductive justice in the time of COVID-19: a systematic review of the indirect impacts of COVID-19 on sexual and reproductive health - Trena I. Mukherjee; Angubeen G. Khan; Anindita Dasgupta; Goleen Samari (BMC, 2021)
Plain English summary The impact of respiratory epidemics, like COVID-19 on women and girls' sexual and reproductive health (SRH) is not yet known. This review applies a reproductive justice framework, to systematically review the impact of respiratory epidemics on SRH, in order to examine the impact of COVID-19 on equitable, sustained access to quality SRH services for all populations. This framework highlights the right to reproductive autonomy, including the right to have an abortion, conceive, bear and raise children; and is inclusive of the intersectionality of race, class and gender. This review includes original, peer-reviewed research related to COVID-19 and women and girls' SRH through May 31, 2021, and consisted of title and abstract screening, full-text screening, and data abstraction. Overall, twenty-four studies met eligibility criteria. Results emphasize that the COVID-19 pandemic resulted in service disruptions that effected access to abortion, contraceptives, HIV/STI testing, and changes in changes in sexual behaviors, menstruation, and pregnancy intentions. These findings highlight the urgent need to enact policies that ensure equitable, timely access to quality SRH services for women and girls, despite pandemic response policies. This review also highlights opportunities to better understand how COVID-19 related disruptions in SRH service provision, access and/or utilization have impacted underserved populations and those with intersectional identities, who faced SRH inequities prior to the COVID-19 pandemic. More research is needed to understand the indirect impact of COVID-19 and epidemic control measures on a wider range of SRH outcomes (e.g., menstrual disorders, fertility services, gynecologic oncology) in the long-term.